Methyl purine ferulic acid aromatized water magnesite composite material as well as preparation method and application thereof
By hybridizing ferulic acid and hydromagnesite powder and adsorbing it with methylpurine derivatives, a methylpurine aromatized ferulic acid-based hydromagnesite composite material is formed, which solves the problem of silane in the existing technology. The coupling agent is not resistant to burning and has a single function. It realizes efficient modification of the composite powder and improves its flame retardant, smoke suppression and char-forming properties.
Patent Information
- Application Number
- CN202411041236.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-01-21
AI Technical Summary
The silane coupling agent used in the prior art to modify natural mineral powders has problems such as inflammability resistance, single function, poor thermal stability and poor carbon-forming performance.
By hybridizing ferulic acid and hydromagnesite powder, and adsorbing it with methylpurine derivatives, a methylpurine aromatized ferulic acid-based hydromagnesite composite material is achieved, which realizes the natural Modification of the surface of hydromagnesite powder.
This method effectively shields the hydroxyl position point on the surface of the magnesium powder, reduces its surface polarity, improves the activation rate of composite powder, improves its flame retardant and smoke suppression characteristics, improves the performance of carbon forming and processing liquidity, reduces processing cost.
Smart Images

Figure CN119331309A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of green material preparation, and in particular to a methyl purine ferulic acid aromatized hydromagnesia composite material and a preparation method and application thereof. Background Art
[0002] The extensive use of natural organic products can effectively slow down the rapid consumption of petrochemical resources and has a great promoting effect on material innovation and sustainable environmental protection development. At present, natural organic products are mostly concentrated in the preparation of traditional Chinese medicine preparations and functional medicinal drinks. They are also commonly found in various nutritional supplements and health oral liquid ingredients, and are indispensable in daily life. In addition, with the improvement of large-scale plant cultivation and extraction technology, its output and production capacity have reached the scale of industrial application, and the cost has been greatly reduced and controllable. At the same time, natural inorganic mineral powders have great advantages in green environmental protection, and have significant advantages in sources and production costs. Among them, natural hydromagnesite powder is a good basic magnesium carbonate composite powder with good reinforcement, filling, flame retardant, smoke suppression and other properties. However, after physical processing (especially after ultrafine processing), this type of powder has a large number of hydroxyl groups on the surface, which is easy to absorb moisture and agglomerate, or even agglomerate, which seriously restricts the storage of this type of powder and its large-scale application in the fields of electrical cables, automobile industry, etc., and its surface structure needs to be changed urgently. Polymer blending and alloying is one of the efficient measures to improve composite materials. Among them, low-density polyethylene (LDPE) has excellent cold and low temperature resistance, electrical insulation and chemical stability, etc. Thermoplastic elastomer (TPE) has good ductility, bending resistance, thermal oxidation aging resistance, etc. It is a saturated rubber formed by the copolymerization of ethylene, propylene and a small amount of diene monomers. It has good cold resistance, ozone resistance and discharge stability. It has significant advantages in the production of special cables and high-end cables. However, LDPE / TPE mostly presents a lower polarity and is difficult to be compatible with high-polarity natural hydromagnesite, and its dispersion effect is poor. Not only that, as a third-generation functional composite material that is prone to fire, LDPE / TPE alloys need to add relevant functional additives during the manufacturing process, so that the composite material not only has good flame retardant safety characteristics, but also its processing characteristics and carbonization performance can be greatly improved.
[0003] In order to adapt to the objective polarity of low-polarity cable masterbatch, the traditional method is to use a large number of various silane coupling agents to shield the hydroxyl groups on the surface of mineral powders. However, this type of coupling agent itself is not resistant to ablation and has a single function, and its thermal stability and carbon-forming properties are poor. Summary of the invention
[0004] The purpose of the present invention is to provide a methyl purine ferulic acid aromatized hydromagnesite composite material and a preparation method and application thereof, so as to solve the problems of poor burning resistance, single function, poor thermal stability and poor carbon forming performance of the silane coupling agent used for modifying natural mineral powder in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a methyl purine ferulic acid aromatized hydromagnesia composite material, comprising the following steps:
[0007] 1) mixing ferulic acid, a first solvent and hydromagnesite powder, and performing hybridization to obtain ferulic acid hybridized hydromagnesite;
[0008] 2) Mixing the ferulic acid hybrid hydromagnesium, the methyl purine derivative and the second solvent for adsorption to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material.
[0009] Preferably, the ratio of ferulic acid to hydromagnesite powder in step 1) is 0.1-3.0 mol:10 kg;
[0010] The median particle size D of the hydromagnesite powder 50 =0.9~3.8μm.
[0011] Preferably, in step 1), the first solvent is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1:1 to 50;
[0012] The alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
[0013] Preferably, the hybridization temperature in step 1) is 60-120° C. and the time is 0.1-1.0 h.
[0014] Preferably, in step 2), the usage ratio of the methyl purine derivative to the ferulic acid hybrid hydromagnesite powder is 0.5-5 mol:10 kg;
[0015] The methyl purine derivatives are
[0016] Preferably, in step 2), the second solvent is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1 to 50:1;
[0017] The alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
[0018] Preferably, the adsorption temperature in step 2) is 40-100° C. and the adsorption time is 10-100 min.
[0019] The present invention also provides a methyl purine ferulic acid aromatized hydromagnesia composite material prepared by the above preparation method, wherein the median particle size D 50 =1.1~4.0μm.
[0020] The present invention also provides an application of a methyl purine ferulic acid aromatized hydromagnesia composite material in the preparation of a low-polarity cable masterbatch, comprising the following steps:
[0021] The thermoplastic elastomer and low-density polyethylene are first kneaded, the obtained product is mixed with dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesium composite material, and then molded after second kneading to obtain low-polarity cable masterbatch.
[0022] Preferably, the mass ratio of the thermoplastic elastomer, low-density polyethylene, dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesia composite material is 24:56:3:5:8-20;
[0023] The thermoplastic elastomer is a polyolefin thermoplastic elastomer and / or a styrene thermoplastic elastomer.
[0024] The present invention has at least the following beneficial effects:
[0025] (1) The present invention provides a methyl purine derivative hybrid ferulic acid-based hydromagnesite composite material (MP-FA-NHM). The present invention uses ferulic acid to coat the surface of natural hydromagnesite, which can effectively shield the hydroxyl sites on its surface, help reduce its surface polarity, and improve the activation rate of the composite powder. Further, natural methyl purine compounds are attached to the outer layer to form a coating layer on the surface of natural hydromagnesite, which can significantly reduce its adsorption effect on processing aids and greatly reduce processing costs. In addition, natural purine compounds have a typical polyaromatic heterocyclic structure (especially the presence of nitrogen heterocyclic rings), which can greatly improve the flame retardancy and Smoke suppression properties, rapidly cross-linking into rings during combustion and further carbonizing, the natural hydromagnesite inside the composite material will quickly form a large amount of MgO ceramic precursor during combustion, which has good heat resistance and can be used as an inorganic ablation-resistant skeleton to support the external carbon layer, thereby forming a good physical barrier layer. The introduction of nitrogen elements can form an internal and external synergistic effect with the internal hydromagnesite powder, fully combining the heat absorption and smoke suppression of inorganic mineral powders and the rapid carbonization and low mobility of organic methyl purine derivatives. This type of composite powder has great advantages in rapid carbonization, physical barrier, promotion of carbon layer crystallization, synergistic smoke suppression, and enhanced processing fluidity.
[0026] (2) The present invention constructs a functional composite material - methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM) by combining chemical modification and physical adsorption. The yield is high, the preparation process is simple and easy, and it is suitable for industrial production. The obtained composite material (MP-FA-NHM) is white or off-white powder, and the whiteness control of the product is relatively good. It can effectively expand the function enhancement and value enhancement efficiency of natural plant extracts in natural mineral powders, strengthen the application scope of natural plant extracts, and organically integrate the multiple functions of natural organic functional molecules and natural inorganic mineral powders.
[0027] (3) The raw materials used in the present invention are all from nature, mainly plant extracts and natural stone mineral powder, which have the advantages of being green, renewable, degradable and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation principle of methyl purine aromatization ferulic acid-based hydromagnesia composite material;
[0029] Figure 2 This is a schematic structural diagram of the methyl purine aromatized ferulic acid-based hydromagnesia composite material prepared in Example 1;
[0030] Figure 3 This is the SEM image of the methyl purine aromatized ferulic acid-based hydromagnesium composite material prepared in Example 1. DETAILED DESCRIPTION
[0031] like Figure 1 As shown, the present invention provides a method for preparing a methyl purine ferulic acid aromatized hydromagnesia composite material, comprising the following steps:
[0032] 1) mixing ferulic acid, a first solvent and hydromagnesite powder, and performing hybridization to obtain ferulic acid hybridized hydromagnesite;
[0033] 2) Mixing the ferulic acid hybrid hydromagnesium, the methyl purine derivative and the second solvent for adsorption to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material.
[0034] In the present invention, the mixing order of the ferulic acid, the first solvent and the hydromagnesite powder in step 1) is preferably to first dissolve the ferulic acid in the first solvent to obtain a ferulic acid solution, and then add the ferulic acid solution to the hydromagnesite powder in the form of a spray.
[0035] In the present invention, the concentration of the ferulic acid solution is preferably 0.5 to 5 mol / L, more preferably 1 to 4 mol / L, and even more preferably 1 to 2 mol / L.
[0036] In the present invention, the spray rate is preferably 5 to 30 mL / min, more preferably 10 to 25 mL / min, and even more preferably 15 to 20 mL / min.
[0037] In the present invention, the usage ratio of ferulic acid to hydromagnesite powder in step 1) is 0.1-3.0 mol:10 kg, preferably 0.5-2.5 mol:10 kg, more preferably 1.0-2.0 mol:10 kg, and more preferably 1.5 mol:10 kg.
[0038] In the present invention, the hydromagnesite powder is derived from natural hydromagnesite ore, and the pure physical method stone ore powder is obtained by multiple physical classification and crushing. It is purchased from Sanxing Mining in Dandong, Liaoning Province. The main component is 3MgCO3·Mg(OH)2·3H2O. The median particle size of the hydromagnesite powder is D 50 = 0.9 to 3.8 μm, preferably D 50 = 1.2 to 3.5 μm, more preferably D 50 =1.5 to 3.0 μm, more preferably D 50 =1.6~2.3μm.
[0039] In the present invention, in step 1), the first solvent is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1:1-50, preferably 1:10-40, more preferably 1:20-30, and more preferably 1:25.
[0040] In the present invention, the alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
[0041] In the present invention, the hybridization temperature in step 1) is 60-120°C, preferably 70-110°C, more preferably 80-100°C, and more preferably 90°C; the duration is 0.1-1.0h, preferably 0.25-0.75h, and more preferably 0.5h.
[0042] In the present invention, the hybridization is preferably carried out under stirring conditions, and the stirring rate is preferably 50 to 800 r / min, more preferably 100 to 500 r / min, and more preferably 200 to 400 r / min.
[0043] In the present invention, after the hybridization in step 1) is completed, the step of dusting and drying the ferulic acid hybridized hydromagnesite is also included. The dusting is preferably carried out by a cyclone separator. The power of the cyclone separator is preferably 100 to 800 W, the rotation speed is preferably 500 to 2500 r / min, and the air volume range is preferably 30 to 200 m 3 / h; the drying method is preferably blast drying, the drying temperature is preferably 60-100°C, the drying power is preferably 1000-3000W, the air flow rate during drying is preferably 1-5m / s, and the drying time is preferably 0.1-0.8h.
[0044] In the present invention, the order of mixing the ferulic acid hybrid hydromagnesium, the methyl purine derivatives and the second solvent in step 2) is preferably to first mix the methyl purine derivatives with the second solvent to prepare a methyl purine derivative solution, and then add the methyl purine derivative solution to the ferulic acid hybrid hydromagnesium in a spraying manner.
[0045] In the present invention, the concentration of the methyl purine derivative solution is preferably 1 to 10 mol / L, and more preferably 2 to 8 mol / L.
[0046] In the present invention, the spraying speed is preferably 10 to 80 mL / min, more preferably 30 to 60 mL / min, and even more preferably 40 to 50 mL / min.
[0047] In the present invention, the usage ratio of the methyl purine derivatives to the ferulic acid hybrid hydromagnesite powder in step 2) is 0.5-5 mol:10 kg, preferably 0.8-3 mol:10 kg, and more preferably 1-2 mol:10 kg.
[0048] When the dosage ratio of methyl purine derivatives to ferulic acid-based hydromagnesia composite powder is lower than 0.5 mol: 10 kg, the amount of methyl purine derivatives added is too low, and it is difficult to effectively coat and further modify the ferulic acid-based hydromagnesia composite powder. The coating amount of the outer layer of methyl purine derivatives is very limited, which is not conducive to the surface modification and functional enhancement of the composite powder. On the other hand, when the ratio of methyl purine derivatives to ferulic acid-based hydromagnesia composite powder is higher than 5 mol: 10 kg, it may cause the surface methyl purine derivative coating amount to be too large, the outer layer mutual physical adsorption effect is weak, and it is easy to be peeled off during processing, which ultimately reduces the scattered peeling of the external methyl purine derivatives during processing. On the other hand, multiple ferulic acid-based hydromagnesia composite powder particles may be wrapped together, resulting in passive wrapping and aggregation, which becomes a stress concentration point when used to prepare cable materials, resulting in defects, which is not conducive to the improvement of the mechanical properties, dispersion properties, flame retardancy, smoke suppression properties and internal and external synergistic effects of the cable masterbatch.
[0049] In the present invention, the methyl purine derivative is
[0050] In the present invention, the second solvent in step 2) is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1 to 50:1, preferably 10 to 40:1, and more preferably 20 to 30:1.
[0051] In the present invention, the alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
[0052] In the present invention, the adsorption temperature in step 2) is 40-100°C, preferably 50-90°C, more preferably 60-80°C, and more preferably 70°C; the adsorption time is 10-100min, preferably 20-80min, more preferably 30-70min, and more preferably 40-60min; the stirring rate is 500-1500r / min, more preferably 600-1200r / min, and more preferably 700-1000r / min; until the addition is completed, stirring is continued for 0.1-1.0h, more preferably 0.2-0.8h, and more preferably 0.3-0.7h.
[0053] In the present invention, after the adsorption in step 2) is completed, the steps of dust removal, precipitation, impregnation and drying of the methyl purine aromatized ferulic acid-based hydromagnesium composite material are also included. The dust removal is preferably carried out by a cyclone separator. The power of the dust removal is preferably 200 to 1000 W, the rotation speed is preferably 800 to 3000 r / min, and the air volume range is preferably 50 to 250 m 3 / h, preferably, the dust removal is repeated 1 to 3 times; the precipitation temperature is preferably 1 to 10°C, and the time is preferably 0.5 to 6.0h; the impregnation is preferably placing the precipitated methyl purine aromatization ferulic acid-based hydromagnesium composite material in a flowing mixed solvent for immersion, and the flow rate of the mixed solvent during the immersion is preferably 1 to 5m / s, and the immersion time is 0.1 to 0.5h; the drying is preferably freeze-drying, the freeze-drying temperature is preferably -40 to 0°C, the time is preferably 8 to 48h, and the power is preferably 1000 to 3000W.
[0054] In the present invention, the mixed solvent for immersion is a mixed solvent of alcohol and water, wherein the volume ratio of water to alcohol is 1 to 100:1, preferably 20 to 80:1, and more preferably 40 to 60:1.
[0055] In the present invention, the alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
[0056] The present invention also provides a methyl purine ferulic acid aromatized hydromagnesia composite material prepared by the above preparation method, wherein the median particle size D 50 =1.1~4.0μm, preferably D 50 =1.4 to 3.7 μm, more preferably D 50 =1.7 to 3.2 μm, more preferably D 50 =1.8~2.5μm.
[0057] The present invention also provides an application of a methyl purine ferulic acid aromatized hydromagnesia composite material in the preparation of a low-polarity cable masterbatch, comprising the following steps:
[0058] The thermoplastic elastomer and low-density polyethylene are first kneaded, the obtained product is mixed with dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesium composite material, and then molded after second kneading to obtain low-polarity cable masterbatch.
[0059] In the present invention, the mass ratio of the thermoplastic elastomer, low-density polyethylene, dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesia composite material is 24:56:3:5:8 to 20, preferably 24:56:3:5:10 to 18, more preferably 24:56:3:5:12 to 16, and more preferably 24:56:3:5:14 to 15.
[0060] In the present invention, the thermoplastic elastomer is a polyolefin-based thermoplastic elastomer and / or a styrene-based thermoplastic elastomer.
[0061] In the present invention, the temperature of the first kneading is preferably 110 to 150° C., and the time is preferably 3 to 10 minutes.
[0062] In the present invention, the temperature of the second kneading is preferably 110-130° C., and the time is preferably 1-8 min.
[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0064] Example 1
[0065] (1) 194.2 g (1 mol) of ferulic acid was dissolved in a mixed solvent of methanol and secondary purified water (the volume ratio of methanol to secondary purified water was 1:25), and stirred at 50°C and 500 r / min for 1.0 h to obtain a ferulic acid solution with a concentration of 1 mol / L; 10 kg, D 50=1.6μm ultrafine hydromagnesite powder is placed in a high-speed mixer, and the ferulic acid solution is added to the ultrafine hydromagnesite powder in a spraying manner at room temperature (25°C) and 300r / min. The spraying rate is 15mL / min. After the spraying is completed, the system is heated to 100°C and stirred for 0.5h for hybridization. After the hybridization is completed, the mixture is cooled to room temperature and a cyclone separator is used for dust removal. The power of the cyclone separator is 400W, the speed is 1500r / min, and the air volume range is 100m 3 / h, and the dust-free reactant is blown to dry, the blown drying temperature is 80°C, the air flow rate during drying is 3m / s, the drying power is 2000W, and ferulic acid hybrid hydromagnesite (FA-NHM) is obtained after drying for 0.4h.
[0066] (2) 450.4 g (2.5 mol) of 1,3-dimethylxanthine was dissolved in a mixed solvent of methanol and secondary purified water (the volume ratio of methanol to purified water was 20:1), and stirred at 60° C. and 1200 r / min for 1.0 h to obtain a 1,3-dimethylxanthine solution with a concentration of 5 mol / L;
[0067] The 1,3-dimethylxanthine solution was added to 10 kg of ferulic acid hybrid hydromagnesium (FA-NHM) by spraying and stirred at a rate of 800 r / min. The temperature of the system was 60 ° C and the spraying rate was 40 mL / min. After the addition was completed, stirring was continued for 0.5 h for adsorption. After the adsorption was completed, the mixed product was successively dedusted, precipitated, impregnated and dried. First, a cyclone separator was used for dedusting with a power of 500 W, a rotation speed of 2000 r / min, and an air volume range of 150 m 3 / h, after repeated dust removal for 2 times, the composite powder was placed at low temperature (5℃) for 3.0h for precipitation. After precipitation, the composite powder was placed in a mixed solution of flowing water and methanol for 0.3h. The volume ratio of water to methanol was 50:1, and the flow rate of the mixed solution was 3m / s. After immersion, the composite powder was freeze-dried at -20℃ for 28h, and the freezing power was 2000W to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM). The median particle size of the product was D 50 =1.8μm.
[0068] The microscopic morphology of the methyl purine aromatized ferulic acid-based hydromagnesium composite material prepared in this example was characterized by a scanning electron microscope. Figure 3 As shown in the figure, it can be seen that there is a relatively dense irregular coating layer on the surface of natural hydromagnesite powder.
[0069] Example 2
[0070] (1) 19.4 g (0.1 mol) of ferulic acid was dissolved in a mixed solvent of ethanol and secondary purified water (the volume ratio of ethanol to secondary purified water was 1:1), and stirred at 40°C and 200 r / min for 3.0 h to obtain a ferulic acid solution with a concentration of 0.5 mol / L; 10 kg, D 50 =1.6μm ultrafine hydromagnesite powder is placed in a high-speed mixer, and the ferulic acid solution is added to the ultrafine hydromagnesite powder in a spraying manner at room temperature (25°C) and 50r / min. The spraying rate is 5mL / min. After the spraying is completed, the system is heated to 60°C and stirred for 1h for hybridization. After the hybridization is completed, the mixture is cooled to room temperature and a cyclone separator is used for dust removal. The power of the cyclone separator is 100W, the speed is 500r / min, and the air volume range is 30m 3 / h, and the dust-free reactant is blown to dry, the blown drying temperature is 60°C, the air flow rate during drying is 1m / s, the drying power is 1000W, and ferulic acid hybrid hydromagnesite (FA-NHM) is obtained after drying for 0.8h.
[0071] (2) dissolving 180.2 g (1 mol) of 3,7-dimethylxanthine in a mixed solvent of ethanol and secondary purified water (the volume ratio of ethanol to purified water is 1:1), stirring at 40° C. and 1000 r / min for 2.0 h to obtain a 3,7-dimethylxanthine solution with a concentration of 1 mol / L;
[0072] The 3,7-dimethylxanthine solution was added to 10 kg of ferulic acid hybrid hydromagnesite (FA-NHM) by spraying and stirred at a rate of 1500 r / min. The temperature of the system was 40 °C and the spraying rate was 10 mL / min. After the addition was completed, stirring was continued for 1.0 h for adsorption. After the adsorption was completed, the mixed product was successively dedusted, precipitated, impregnated and dried. First, a cyclone separator was used for dedusting with a power of 200 W, a rotation speed of 800 r / min, and an air volume range of 50 m 3 / h, after repeated dust removal for 3 times, the composite powder was placed at low temperature (1°C) for 0.5h for precipitation. After precipitation, the composite powder was placed in a mixed solution of flowing water and methanol for 0.1h. The volume ratio of water to methanol was 1:1, and the flow rate of the mixed solution was 1m / s. After immersion, the composite powder was freeze-dried at -40°C for 8h, and the freezing power was 1000W to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM). The median particle size D 50 =1.8μm.
[0073] Example 3
[0074] (1) 582.6 (3 mol) of ferulic acid was dissolved in a mixed solvent of propanol and secondary purified water (the volume ratio of ethanol to secondary purified water was 1:50), and stirred at 60°C and 1000 r / min for 0.1 h to obtain a ferulic acid solution with a concentration of 5 mol / L; 10 kg, D 50 =1.6μm ultrafine hydromagnesite powder is placed in a high-speed mixer, and the ferulic acid solution is added to the ultrafine hydromagnesite powder in a spraying manner at room temperature (25°C) and 800r / min. The spraying rate is 30mL / min. After the spraying is completed, the system is heated to 120°C and stirred for 0.1h for hybridization. After the hybridization is completed, the mixture is cooled to room temperature and a cyclone separator is used for dust removal. The power of the cyclone separator is 800W, the speed is 2500r / min, and the air volume range is 200m 3 / h, and the dust-free reactant is blown to dry, the blown drying temperature is 100°C, the air flow rate during drying is 5m / s, the drying power is 3000W, and ferulic acid hybrid hydromagnesite (FA-NHM) is obtained after drying for 0.1h.
[0075] (2) dissolving 901 g (5 mol) of 1,3-dimethylxanthine in a mixed solvent of alcohol and secondary purified water (the volume ratio of ethanol to purified water is 50:1), stirring at 70° C. and 2200 r / min for 0.1 h to obtain a 1,3-dimethylxanthine solution with a concentration of 10 mol / L;
[0076] The 1,3-dimethylxanthine solution was added to 10 kg of ferulic acid hybrid hydromagnesium (FA-NHM) by spraying and stirred at a rate of 500 r / min. The temperature of the system was 100 °C and the spraying rate was 80 mL / min. After the addition was completed, stirring was continued for 0.1 h for adsorption. After the adsorption was completed, the mixed product was successively dedusted, precipitated, impregnated and dried. First, a cyclone separator was used for dedusting with a power of 1000 W, a rotation speed of 3000 r / min, and an air volume range of 250 m 3 / h, after repeated dust removal for 3 times, the composite powder was placed at low temperature (10℃) for 6h for precipitation. After precipitation, the composite powder was placed in a mixed solution of flowing water and methanol for 0.5h. The volume ratio of water to methanol was 100:1, and the flow rate of the mixed solution was 5m / s. After immersion, the composite powder was freeze-dried at -0℃ for 48h, and the freezing power was 3000W to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM). The median particle size of the product was D 50 =1.8μm.
[0077] Comparative Example 1
[0078] Step (1) is the same as in Example 1.
[0079] (2) dissolving 18.0 g (0.1 mol) of 1,3-dimethylxanthine in a mixed solvent of methanol and secondary purified water (the volume ratio of methanol to purified water is 20:1), stirring at 60° C. and 1200 r / min for 1.0 h to obtain a 1,3-dimethylxanthine solution with a concentration of 5 mol / L;
[0080] The remaining steps are the same as in Example 1.
[0081] Comparative Example 2
[0082] Step (1) is the same as in Example 1.
[0083] (2) dissolving 1442.8 g (8 mol) of 1,3-dimethylxanthine in a mixed solvent of methanol and secondary purified water (the volume ratio of methanol to purified water is 20:1), stirring at 60° C. and 1200 r / min for 1.0 h to obtain a 1,3-dimethylxanthine solution with a concentration of 5 mol / L;
[0084] The remaining steps are the same as in Example 1.
[0085] Comparative Example 3
[0086] Natural hydromagnesite powder, the median particle size of the product is D 50 =1.6μm.
[0087] The activation rate, oil absorption value and contact angle of the methyl purine aromatized ferulic acid-based hydromagnesia composite material (MP-FA-NHM) prepared in Examples 1 to 3 and the methyl purine aromatized ferulic acid-based hydromagnesia composite material (MP-FA-NHM) in Comparative Examples 1 to 3, and the natural hydromagnesia powder were tested. The test method is as follows:
[0088] Activation rate: The dry powder is tested by weighing method.
[0089] Oil absorption value: tested in accordance with DB / T5211.15-2014 standard.
[0090] Contact angle: The contact angle of the sample was measured using a contact angle meter.
[0091] The test results are shown in Table 1.
[0092] Table 1 Performance test results of the products prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0093]
[0094]
[0095] From the test results of Examples 1 to 3 and Comparative Example 3 in Table 1, it can be found that by introducing ferulic acid and methyl purine derivatives, multi-layer and multi-component modification of natural hydromagnesite powder can be achieved, the activation rate of the obtained composite powder is significantly improved and the oil absorption value is significantly reduced, and the contact angle of the obtained composite powder is also significantly improved, the highest from 27.8° to 101.5°, achieving a transition from hydrophilicity to hydrophobicity. From the test results of the composite powders prepared by Comparative Examples 1 to 3, it can be seen that when the proportion of methyl purine derivatives on the surface is not appropriate, the activation rate and oil absorption performance of the final composite powder are limited. In terms of contact angle, due to the introduction of hydrophobic structure methyl purine, the contact angle of the composite powder is improved to a certain extent, but the improvement effect is poor. In summary, after adding appropriate proportions of ferulic acid and methyl purine derivatives to modify natural hydromagnesite, the comprehensive performance of the composite powder (MP-FA-NHM) is significantly improved, which is beneficial to reduce the surface energy of the composite powder, making the composite powder show typical hydrophobicity and low polarity, which helps to improve the adsorption of the composite powder to processing aids and greatly reduce the processing cost. When the proportion of the added methyl purine derivatives is not appropriate, the surface performance of the resulting composite powder is limited.
[0096] The methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM) prepared in Examples 1 to 3 and the methyl purine aromatized ferulic acid-based hydromagnesium composite material (MP-FA-NHM) in Comparative Examples 1 to 3, and natural hydromagnesium ore powder were added to TPE / LDPE material to prepare a cable material, and the performance of the cable material was tested, and the specific method was as follows:
[0097] At 150°C, 24wt% of TPE and 56wt% of LDPE (TPE is V5502, Suzhou Hongshuo, LDPE is 2426H, Sinopec, and the mass ratio of TPE to LDPE is 30:70) are first kneaded for 5 minutes, and then 3 parts of dioctyl phthalate (DOP) and 5 parts of paraffin are added, and 15wt% of the methyl purine aromatized ferulic acid-based hydromagnesite composite material (MP-FA-NHM) prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and the natural hydromagnesite powder described in Comparative Example 3 are added, and then kneaded at 110°C for 5 minutes, and then taken out and placed on an open mill for fixed molding, the temperature is controlled to be 160°C, the back pressure is 10MPa, the hydraulic molding time is 6min, and then cold pressed for 8min to prepare various test specimens for standby use.
[0098] Thermal gravimetric test: nitrogen atmosphere, heating rate 20℃ / min, 30~600℃.
[0099] Limiting oxygen index: ASTM D2863 test.
[0100] Vertical Burning: ASTM D3801-2010.
[0101] Melt index: GB / T3682-2000, 190°C, load 2.16kg.
[0102] Tensile strength test: GB / T1040-2004, at 23±2℃.
[0103] Raman spectrum test: Bruker FRS-100S, 500~3000cm -1 , I D Located at 1340cm -1 The D band peak, I G Located at 1570cm -1 The G-band peak.
[0104] The test results are shown in Table 2.
[0105] Table 2 Performance test results of TPE / LDPE composite materials prepared using the powders obtained in Examples 1 to 3 and Comparative Examples 1 to 3
[0106]
[0107] By comparing the data on the carbon residue quality of the composite materials prepared by the powders described in Examples 1 to 3 and Comparative Example 3, it can be seen that when ferulic acid and methyl purine derivatives are added in appropriate proportions, the carbon residue quality of the composite material can be significantly improved, and the maximum value increases from 11.3% to 26.8%. It can be seen that the successive modification of ferulic acid and methyl purine derivatives can effectively promote the increase in the number of carbon layers of the composite material, thereby achieving a better physical barrier effect. In terms of combustion performance, the LOI value of the composite material increases from 22.5% to a maximum of 30.2%, which transforms the composite material from a combustible material to a flame retardant material. It can be seen that the flame retardant performance is effectively improved; at the same time, in the vertical combustion test, the composite powders added with ferulic acid and methyl purine derivatives can make the vertical combustion of the composite material pass the V-0 level. In contrast, the addition of composite powders that have not been effectively modified in the composite material will make it difficult to pass the V-0 level, and the most High can only pass V-1 grade; in terms of processing performance, the introduction of ferulic acid and methyl purine derivatives can improve the melt index of the composite material to a certain extent, making it have a higher quality of outflow in the same time. This may be because the composite powder can be used as a lubricant after introduction to promote the relative flow and slip of the molecular chain. The composite powder without effective surface modification is added to the composite matrix, and weak bonds such as hydrogen bonds may occur, causing it to undergo breakable chemical crosslinking or physical entanglement, and its processing fluidity is poor; in the process of mechanical tensile testing, the introduction of ferulic acid and methyl purine derivatives in appropriate proportions into the composite powder can improve the dispersion and compatibility of the composite powder in the polymer matrix, and effectively improve the tensile resistance of the composite material; in terms of carbonization effect, the introduction of ferulic acid and methyl purine derivatives in appropriate proportions can significantly promote the improvement of the degree of ordering of the carbon layer, that is, the formation of more crystalline carbon layers, which are I compared with the amorphous carbon layer. D / I G It can be reduced from 1.68 to 0.76 at most, and its crystallinity is greatly improved, which can better resist the impact of airflow, mass flow and heat flow, and effectively improve the physical barrier property. This shows that the introduction of ferulic acid and methyl purine derivatives can strengthen the synergistic effect with the natural hydromagnesite core, and thus play a significant role in flame retardancy and improving the quality and quantity of residual carbon. In contrast, in Comparative Examples 1 to 2, both the carbonization quality and quantity are inferior to Examples 1 to 3, and the combustion performance test is not as obvious as that of Examples 1 to 3. The performance improvement in tensile strength and processing fluidity is also limited. This may be because after the introduction of an inappropriate proportion of methyl purine derivatives, it is difficult to further effectively modify the natural hydromagnesite powder, and the internal and external synergistic effects are difficult to play well.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material, characterized in that: The following steps are involved: 1) mixing ferulic acid, a first solvent and hydromagnesite powder, and performing hybridization to obtain ferulic acid hybridized hydromagnesite; 2) Mixing the ferulic acid hybrid hydromagnesium, the methyl purine derivative and the second solvent for adsorption to obtain a methyl purine aromatized ferulic acid-based hydromagnesium composite material.
2. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 1, characterized in that: The ratio of ferulic acid to hydromagnesite powder in step 1) is 0.1-3.0 mol:10 kg; The median particle size D of the hydromagnesite powder 50 =0.9~3.8μm.
3. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 2, characterized in that: In step 1), the first solvent is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1:1 to 50; The alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
4. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 2 or 3, characterized in that: The hybridization temperature in step 1) is 60-120° C. and the time is 0.1-1.0 h.
5. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 4, characterized in that: In step 2), the ratio of the methyl purine derivative to the ferulic acid hybrid hydromagnesite powder is 0.5-5 mol:10 kg; The methyl purine derivatives are and / or 6. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 5, characterized in that: In step 2), the second solvent is a mixed solvent of alcohol and water, wherein the volume ratio of alcohol to water is 1 to 50:1; The alcohol includes one or more of methanol, ethanol, propanol, isopropanol, ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol.
7. The method for preparing a methylpurine ferulic acid aromatized hydromagnesite composite material according to claim 6, characterized in that: The adsorption temperature in step 2) is 40-100°C and the adsorption time is 10-100 minutes.
8. The methyl purine ferulate acid aromatized hydromagnesia composite material prepared by the method for preparing the methyl purine ferulate acid aromatized hydromagnesia composite material according to any one of claims 1 to 7, characterized in that: The median particle size D of the methyl purine ferulic acid aromatized hydromagnesia composite material 50 =1.1~4.0μm.
9. The use of the methyl purine ferulic acid aromatized hydromagnesia composite material according to claim 8 in the preparation of low-polarity cable masterbatch, characterized in that: The following steps are involved: The thermoplastic elastomer and low-density polyethylene are first kneaded, the obtained product is mixed with dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesium composite material, and then molded after second kneading to obtain low-polarity cable masterbatch.
10. The use of the methyl purine ferulic acid aromatized hydromagnesia composite material according to claim 9 in the preparation of low-polarity cable masterbatch, characterized in that: The mass ratio of the thermoplastic elastomer, low-density polyethylene, dioctyl phthalate, paraffin and methyl purine ferulic acid aromatized hydromagnesium composite material is 24:56:3:5:8-20; The thermoplastic elastomer is a polyolefin thermoplastic elastomer and / or a styrene thermoplastic elastomer.